Management of critically ill obstetric patients: A review - Manpreet Kaur; Preet Mohinder Singh; Anjan Trikha (Wolters Kluwer Medknow Publications, 2017)
Critically ill obstetric patients present a unique challenge as outcome of indwelling life is dependent upon the maternal well-being. Optimal patient management involves early detection and the multidisciplinary treatment by obstetricians, pediatricians, and anesthesiologists based on knowledge of physiological and pathophysiological alterations. This article aims to provide a comprehensive review of the available literature for the management of critically ill obstetric patient and recent update on commonly encountered situations.